Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.1 - Radicals and Radical Functions - Exercise Set - Page 417: 81



Work Step by Step

We are given that $g(x)=\sqrt[3] (x-8)$. Therefore, $g(-19)=\sqrt[3] (-19-8)=\sqrt[3] (-27)=-3$ We know this, because $(-3)^{3}=-3\times-3\times-3=-27$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.